CRIMINAL INVESTIGATION OF FORGED SIGNATURES AND DOCUMENTS (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
This article describes the definitions given by our country's and foreign forensic scientists on the concept of signatures, which is one of the objects of forensic forensic expertise, which is in the leading position among the traditional types of criminalistic expertise. In turn, new proposals regarding these definitions, mutual analysis of signature concepts, uniqueness of signature research, as well as a number of errors regarding the appointment of expertise by the official of the body conducting the pre-investigation investigation, inquiry, investigator, court, in particular, a number of errors and shortcomings are detailed.